Merger Announcements and Insider Trading Activity: An Empirical Investigation - KEOWN, ARTHUR J.; PINKERTON, JOHN M. (Journal of Finance, 1981)
ABSTRACT This paper provides evidence of excess returns earned by investors in acquired firms prior to the first public announcement of planned mergers. The study is distinguished from earlier merger studies in its use of daily holding period returns for the 194 firms sampled. The results confirm statistically what most traders already know. Impending merger announcements are poorly held secrets, and trading on this nonpublic information abounds. Specifically, leakage of inside information is a pervasive problem occurring at a significant level up to 12 trading days prior to the first public announcement of a proposed merger.